Enhanced Interactive Performance of Zoom-In/Out Gestures Using Electrostatic Tactile Feedback on Touchscreens. (8th June 2020) - Wang, Qinglong; Sun, Xiaoying; Cao, Dekun; Liu, Guohong
Abstract: Tactile feedback added to touchscreens provides users with a high-quality interactive experience. The effect of tactile feedback on typical interaction gestures requires to be evaluated. With a custom-designed electrostatic tactile feedback device, we explore the effects of tactile feedback on zoom-in/out gestures and determine the issues satisfied by the relationship between completion time (CT) and index of difficulty (ID). Specifically, we compare the effect of electrostatic tactile feedback on the efficiency and accuracy of zoom-in/out gestures in three conditions, that is, no tactile feedback, linearly increasing tactile feedback force over operation process, and tactile feedback only in a target area. Then, we study the relationship between CT and ID with tactile feedback added to the target area. Results of experimental data from 12 participants show that tactile feedback added only to a target area can significantly increase operational efficiency and accuracy of zoom-in/out gestures. Furthermore, the relationship between CT and ID agrees well with Fitts' law, and the correlation coefficient is larger than 0.9.